2018
DOI: 10.1007/s11033-018-4362-x
|View full text |Cite
|
Sign up to set email alerts
|

Rational design-based engineering of a thermostable phytase by site-directed mutagenesis

Abstract: Phytases are enzymes that hydrolysis phytic acid and makes mineral phosphorus available to animals. Phytases face relatively extreme heating during food processing, thus thermostability plays an important role in industrial applicability of this enzyme. Herein, we report the design of a thermostable phytase with favorable biochemical properties and high enzymatic activity using molecular dynamics and rational design-based molecular engineering. Based on the crystal structure of E. coli phytase, bioinformatics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Molecular dynamics simulations revealed up to 3-fold higher interactions in the active site of both enzymes with bound polyP compared to bound RNA, which may explain the higher rates of the enzymes toward polyP ( Figure 5 ). Structure-based modeling of substrate-enzyme complexes was previously used to guide rational engineering of enzymes such as phytase, 68 lipase, 69 , 70 aminotransferase, 71 and transketolase. 72 In a similar fashion, the structural insights obtained here could contribute to guiding principles toward optimizing the activity of APs for P-polymer dephosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dynamics simulations revealed up to 3-fold higher interactions in the active site of both enzymes with bound polyP compared to bound RNA, which may explain the higher rates of the enzymes toward polyP ( Figure 5 ). Structure-based modeling of substrate-enzyme complexes was previously used to guide rational engineering of enzymes such as phytase, 68 lipase, 69 , 70 aminotransferase, 71 and transketolase. 72 In a similar fashion, the structural insights obtained here could contribute to guiding principles toward optimizing the activity of APs for P-polymer dephosphorylation.…”
Section: Resultsmentioning
confidence: 99%
“…Structural comparisons between the mutant and native phytase revealed that substituting Ser392 with Phe caused two new hydrophobic interactions with Trp 347, which brought about the elevated structural stability of Escherichia coli AppA phytase, as shown in Figure 6. Along with the increase in thermostability, the catalytic efficiency of the mutant was also increased by 25.6% through introducing hydrophobic interactions [34]. Based on the highest B-values, nine substitutions (P41W, V42S, K43L, R181S, E182S, Q285D, K286Y, E384V, R385A) were made and four more substitutions (S80I, Q184A, S342T, E383A) on the surface loop were carried out for protein surface engineering.…”
Section: Escherichia Coli Phytasementioning
confidence: 99%
“…Mutant S392F showed a 25.6% enhancement in catalytic efficiency over that of the native phytase. Structural comparison between S392F and native phytase revealed that substituting Ser-392 with Phe introduced two new hydrophobic interactions with Trp-347 [34].…”
Section: Escherichia Coli Phytasementioning
confidence: 99%
“…However, some sensitive residues hidden in the rigid parts of the protein would escape discovery. Rigid regions are also essential for protein stability, and many strategies had been reported involving modifications at rigid regions with improved protein stability, including removing or pairing of unpaired H-bond donors/acceptors , and charged groups, filling cavities, improving hydrophobic packing, enlarging hydrophobic clusters, and resolving steric strain . If further improvement of the protein stability is desired, it may be necessary to consider sensitive residues in rigid regions in addition to hot spots in flexible regions as multiple mutations may have synergistic effects. …”
Section: Introductionmentioning
confidence: 99%